Mediações urbanas em rotas autobiográficas: processos de formação em Artes a partir dos graffiti do Selo Coletivo (CE) e das Minas de Minas Crew (MG) - Moreira, Antonia Camila Alves (2021)
This thesis addresses the experiences of an art teacher in training who recognizes through the graffiti of two groups of graffiti artists - Selo Coletivo (CE) and Minas de Minas (MG) - issues related to her artistic, professional and identity. The construction of the thesis takes place through first-person writing, with autobiographical fragments, using a set of everyday research resources as a methodology - such as notes, poetry and diagrams, in addition to the use of Narrative Interviews (JOVCHELOVITCH & BAUER, 2002). As a conceptual basis, we present the contributions of Visual Culture (DUNCUN, 2011, GUIMARÃES, 2010, MARTINS, 2011, TOURINHO, 2011 and SÉRVIO, 2014), Narrative Research (HERNÁNDEZ, 2011 and ABRAHÃO, 2010) and black authors such as KILOMBA, (2019) and EVARISTO (2017) to discuss the experiences and artistic practices developed in our artistic and professional trajectory and throughout the PhD. Therefore, the thesis is an open diary composed of reflections and mediation exercises between training routes, routes between 4 Brazilian cities and the images created by the 2 collectives, resulting in the Urban Mediations concept that arises in the research in different formats, images and visualities. Other results are the development of the use and reflection of images in the text, and also the recognition of the author's identity subjectivities.